ANALISIS PENGARUH LINGKUNGAN KERJA, PROMOSI JABATAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA CV. KESUMA JAYA MEDAN - Simbolon, Sahat (UNIKA Santo Thomas, 2020)
This study aims to determine the effect of working environment, job promotion and compensation on the employee’s performance at CV. Kesuma Jaya Medan. This research is conducted at CV. Kesuma Jaya Medan for 8 (eight) months periode of time, starting from January 2019 until August 2019. This study is using stratified random sampling method. The population in this study is the employees in CV. Kesuma Jaya Medan as many as 106 people. The number of sample obtained is 84 people. Methods of data collection in this study is using questionnaires to collect the data for working environment, job promotion, compensation and employee’s performance variable. The technique of data analysis used is validation test, reliability test, description analysis, classic assumption test, multiple linear regression analysis, multiple linear correlation coefficient testhypotesis test partially and simultaneously and coefficient determination. From the description analysis of working environment, job promotion, compensation and employee’s performance variable have been in good category. Partially, working environment, job promotion and compensation has a positive and significant effect on employee’s performance in CV. Kesuma Jaya Medan in which tcount  ttable Simultaneously, there is a positive and significant effect of working environment, job promotion and compensation on employee’s performance in CV. Kesuma Jaya Medan in which Fcount Ftable.. From the coefficient of determination, employee’s performance influenced by working environment, job promotion and compensation by 0,728 or 72,8%. While the remaining 0,272 or 27,2% of employee’s performance is influenced by other variables that are not observed in this study, example leadership, working comitment, organizational culture, etc